Judicial power in a federal system : Canada, United States and Germany / Cristina M. Ruggiero. - Ruggiero, Cristina M., 1972- (Law and society (New York, N.Y.), 2012)
Ruggiero provides a systematic evaluation of the?interdependent nature? of judicial power within three federal systems. She seeks to answer the question: Why are some high courts more powerful than others? By integrating strategic assumptions about the behavior of courts and other political actors and by employing a comparative, historical analysis of court policy-making and legislative responses to said policy-making, Ruggiero tests and refines concepts of court influence as?interdependent?. She finds that the influence of high courts and their decisions are shaped both by?intrinsic? insti.